STEREOTIP DAN PRASANGKA KOMUNIKASI ANTAR PEMERAN FILM KOS-KOSAN DENGAN PESPEKTIF WACANA KRITIS MILLS - Maria Borges, Serilio Verdial; Marta, Rustono Farady; Panggabean, Hana Rochani Gustasari; Briandana, Rizki; Chinmi, Maichel (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Visual media is a very popular communication media in society, with short films being particularly accessible and easily interpreted by viewers. This research aims to analyse a short film titled